2022
DOI: 10.26434/chemrxiv-2022-4hc7q-v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Performance of continuous emission monitoring solutions under single-blind controlled testing protocol.

Abstract: Continuous emission monitoring (CM) solutions promise to accelerate fugitive methane emission mitigation in natural gas infrastructure by detecting large sources sooner than they would be detected in traditional leak surveys. Quantification by CM solutions has also been proposed as the foundation of measurement-based inventories. Herein we present the first published results of CM solutions tested using a consensus protocol. Single-blind testing was performed with controlled releases at a dedicated facility, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
1
13
0
Order By: Relevance
“…While the CMP metrics are a useful framework for providing a method to compare the key characteristics of continuous monitoring systems that are most of interest to oil and gas operators and regulators, our work illuminates some refinements that could be made to further increase the utility of the metrics. Limitations of the CMP methodology to perform classification of detections as TP or FP detections have been identified in other testing programs, 11 suggesting a need to consider the application or use case of the continuous monitoring system under evaluation and to tailor the methodology as appropriate. Defining FPF such that it is not dependent on the number of controlled releases would allow more meaningful comparison between systems tested under very different experimental designs.…”
Section: Emissions Localization Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While the CMP metrics are a useful framework for providing a method to compare the key characteristics of continuous monitoring systems that are most of interest to oil and gas operators and regulators, our work illuminates some refinements that could be made to further increase the utility of the metrics. Limitations of the CMP methodology to perform classification of detections as TP or FP detections have been identified in other testing programs, 11 suggesting a need to consider the application or use case of the continuous monitoring system under evaluation and to tailor the methodology as appropriate. Defining FPF such that it is not dependent on the number of controlled releases would allow more meaningful comparison between systems tested under very different experimental designs.…”
Section: Emissions Localization Resultsmentioning
confidence: 99%
“…Recent evaluation of continuous monitoring systems at METEC included hundreds of individual releases, some lasting up to 8 hours, at emission rates up to 6.39 kg/h. 11 In this study, releases were limited to rates ≤ 2.15 kg/h and durations ≤ 60 minutes. Initial unblind test results indicated that high release rates were not needed to identify the minimum detection threshold and that short durations would provide ample information on detection thresholds.…”
Section: Unblind Release Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…During the eld campaign, the solutions did not provide detection reports using the same email based reporting method as required during METEC testing. 19 Instead, the study team was granted access to the solution's "dashboard", a graphical user interface provided to operators to receive alerts, interact with data, investigate or acknowledge detections, and The original intent of the eld campaign was to utilize the same metrics as METEC CR testing, specically POD, quantication accuracy, and localization accuracy. 19 Since solutions did not provide dened detection reports that could be used for this purpose, the eld team needed to interpret the dashboards' raw data to determine if there was a sucient change in emissions that the presence of excess emissions at the site could be reasonably identied.…”
Section: Psn Solution Datamentioning
confidence: 99%
“…A major investment by the Advanced Research Project Agency-Energy (ARPA-E) has stimulated substantial commercial investment over the last decade in measurement methods to assess emissions using remote sensing techniques, including drones, manned aircraft, and satellite technologies. The increase in investment and method development have been accompanied by extensive testing programs using a wide variety of protocols [10,11], as well as a major Department of Energy-funded program [12,13] to develop standardized test protocols.…”
Section: Introductionmentioning
confidence: 99%